C2H5OH gas sensing based on poly(3-hexylthiophene)/Nb-loaded ZnO nanocomposite films - Viruntachar Kruefu (2018)
Copyright © 2014 Taylor & Francis Group, LLC. The C2H5OH gas sensors were developed using flame-made 0.75mol%Nb/ZnO NPs composite with P3HT as the sensing materials. The composite films of P3HT: 0.75mol% Nb/ZnO NPs in the ratio of 4:1, 3:1, 2:1, 1:1 and 1:2 were prepared by drop casting method onto Al2O3substrates interdigitated with Au electrodes. The sensing films were analyzed by XRD, SEM and EDS. The gas sensing of C2H5OH was studied at the room temperatures. It was found that the composite films P3HT:0.75mol% Nb/ZnO NPs in the ratio of 2:1 showed the highest sensitivity and fast response time towards C2H5OH gas at room temperature.